E-invoicing in EU public procurement as a tool for cross border trade barriers elimination - Oleksandr TSARUK (Eastern European Journal of Regional Studies)
Public Procurement of goods and services always was one of the principal element of e-procurements because it effects economic growth, describes governments' public services and national competitiveness, level of human capital growth in a long run. Furthermore, researching EU policy on e-procurements demands to observe legislature essence and technological models of e-procurement solutions because none of which has not been developed as the universal one yet. Basic European agreements on public procurements and trade, combining with the currently used public procurement models, force to develop a commonly used framework for all EU countries. Monitoring of EU e-procurement system as model for implementation at Eastern partnerships countries was also suggested.